Blood concentration of cyclosporine during early post-transplant period may have influence on the occurrence of chronic graft versus host disease in patients who received allogeneic hematopoietic stem cell transplantation - Park, Silvia (Oncotarget, 2016)
INTRODUCTION: It has rarely been studied that how the blood level of CsA affect the incidence of chronic GVHD after allogeneic hematopoietic stem cell transplantation (allo-HSCT). METHODS: A total of 183 patients who underwent allo-HSCT from an HLA-matched or haplo matched family donors between 2006 and 2014 were reviewed. RESULTS: The average monthly CsA blood concentration (CsA(avr), ng/ml) was calculated in each patient: 0-1, 1-2, and 2-3 months after allo-HSCT. CsA(avr) at the first month showed significant association with the occurrence of moderate to severe cGVHD in multivariate analysis adjusted for gender, age, total body irradiation, anti-thymocyte globulin, acute GVHD ≥ grade 2 and CsA(avr) levels of other periods. The risk of cGVHD development was lowest in patients with CsA(avr) of 200-250 ng/ml when compared to those with CsA(avr) of ≥ 250 or < 200 ng/ml (p=0.003). CONCLUSIONS: CsA level between 200 and 250 mg/ml during the first month after transplantation was significantly associated with the decreased risk of moderate to severe cGVHD.